Detection of Escherichia coli and Pseudomonas aeruginosa using REP-PCR monitoring goat´s milk quality in milking room - Chapaval, Lea; Olivindo, Cellyneude de Souza; Souza, Francisca Geovânia Canafístula de; Alves, Francisco Selmo Fernandes; Frota, Isana Mara Aragão (Comunicata Scientiae, 2010)
The present study was carried out with the objective of applying the REP-PCR sequences on the monitoring of goat milk quality, through the detection of Escherichia coli and Pseudomonas aeruginosa, in samples of milking handlers, goat teats, milk, milk machine and water, for the future establishment and implantation of the system of Hazard Analysis Critical Control Points. Several fingerprints were verified of all isolates collected of the different studied sources (milking handlers, goat teats, milk, milk machine and water). It was observed very similar behaviors of the bands indicating that the isolates can be related as epidemic clones. Hands of the milking handlers were characterized as a critical point of control, because they stand out as initial point of Escherichia coli and Pseudomonas aeruginosa contamination. The technique demonstrated to be efficient for the similarity analysis among individuals of the Escherichia coli and Pseudomonas aeruginosa species, being, therefore, an useful tool for investigation of fails on management and consequently, in the search of more efficient control to avoid or to minimize the spread of pathogenic microorganisms that cause serious illnesses in humans and animals, and can be transmitted through products such as milk and your products.